The Pursuit of Gentility in an Age of Revolution: The Family of Jonathan Worrell - Bittermann, Rusty; McCallum, Margaret (Acadiensis, 2014)
The Worrell family’s half century of connection with Prince Edward Island began in 1803, when Jonathan Worrell, a Barbadian plantation owner living in England, purchased 47,000 acres of land in Kings County. Jonathan’s son, Charles, moved to the Island and managed the estate for more than 40 years, doubling its size. Across these years, the Worrell family dealt with war in the transatlantic world, emancipation of the enslaved peoples who worked their sugar plantations, and demands for an escheat of large landholdings on the Island. This article considers the Worrells’ decision to invest in PEI within that broader context.